2021
DOI: 10.2147/ijgm.s292426
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Values of Epicardial Adipose Tissue Thickness with Right Common Carotid Artery Elasticity and Intima-Media Thickness for Middle-Aged and Elderly Patients with Coronary Heart Disease

Abstract: Background Coronary heart disease (CHD) is the most common cardiovascular disease which greatly threatens the health of middle-aged and elderly people. Objective To explore the correlations of epicardial adipose tissue (EAT) thickness with right common carotid artery elasticity and intima-media thickness (IMT) in middle-aged and elderly patients with CHD by ultrasound. Methods A total of 132 patients diagnosed with CHD by coronary angiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…CHD is a common disease caused by functional and organic stenosis of the coronary arteries, resulting in decreased oxygenated blood in the heart[ 11 ]. CHD occurrence and development are closely related to daily life habits, individual differences in patients, and so on[ 12 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…CHD is a common disease caused by functional and organic stenosis of the coronary arteries, resulting in decreased oxygenated blood in the heart[ 11 ]. CHD occurrence and development are closely related to daily life habits, individual differences in patients, and so on[ 12 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ROC curve analysis of this study showed that the diagnostic value of non-calcified plaque volume and loading for the recurrence of adverse cardiovascular events within 1 year in unstable CHD patients was comparable to that of carotid intima-media thickness, LVEF, hypertension, and so on. The carotid intima-media thickness, LVEF, and hypertension have been confirmed to be good predictors of adverse cardiovascular events (17)(18)(19)(20), which indicates that the use of CCTA to measure the volume and loading of non-calcified plaques is of good value in diagnosing adverse cardiovascular events that recur within 1 year in patients with unstable CHD.…”
Section: Discussionmentioning
confidence: 91%
“…The correlation of EAT with age was statistically significant and is in agreement with several studies. It has been well established that CAD risk in middle-aged and elderly patients is correlated with increased EAT thickness, and regarded as a prominent indicator for diagnosis of CAD among this age group [ 36 ]. As a person ages, the epicardial fat thickness will increase due to redistribution of the fat to the visceral and trunk [ 37 ].…”
Section: Discussionmentioning
confidence: 99%